Treatment outcomes for pediatric pineoblastoma: a single institute experience in Taiwan - Kang, Yu-Mei; Lin, Shih-Chieh; Lee, Yi-Yen; Chang, Feng-Chi; Liang, Muh-Lii; Chen, Hsin-Hung; Liu, Yu-Ming; Wong, Tai-Tong; Chen, Yi-Wei (Therapeutic Radiology and Oncology, 2018)
Background: Our purpose was to evaluate the clinical outcomes of pediatric pineoblastoma patients after multimodality treatment. Methods: The medical records of 11 children with pineoblastomas treated at Taipei Veterans General Hospital between 1991 and 2006 were retrospectively reviewed. There were 7 females (63.6%) and 4 males (36.4%) with a median age at diagnosis of 5.25 years (range, 1.47–16.8 years). Age, sex, symptoms, pathological findings, treatment modalities, failure patterns, recurrence date, death date, and toxicities were recorded. Survival curves were estimated with the Kaplan-Meier method, and univariate Cox proportional hazards models were used to identify possible risk factors. Results: The median overall survival was 2.3 years, with 2- and 5-year survival rates of 63.6% and 36.4%, respectively. Eight patients (72.7%) died after serial treatments, and extensive seeding with multi-organ failure was the most common failure pattern. Three patients (27.2%) were alive without disease recurrence. Kaplan-Meier survival curves showed a significant difference (P